2019 IEEE/CVF International Conference on Computer Vision Workshop (ICCVW) 2019
DOI: 10.1109/iccvw.2019.00196
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Real-Time Camera Based Estimation of Heart Rate and Its Variability

Abstract: Remote photo-plethysmography (rPPG) uses a remotely placed camera to estimating a person's heart rate (HR). Similar to how heart rate can provide useful information about a person's vital signs, insights about the underlying physio/psychological conditions can be obtained from heart rate variability (HRV). HRV is a measure of the fine fluctuations in the intervals between heart beats. However, this measure requires temporally locating heart beats with a high degree of precision. We introduce a refined and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…As can be observed from performing rPPG using the SPAD camera and the tachogram estimation techniques described in Section 3.3.3, one could retrieve some information on a relatively hard task as remotely estimating the sympathovagal balance. In particular, the best results are achieved at the 550 nm wavelength with a average RMSE of 0.8, which is a state of the art result as reported in [32]. Respiration Rate Lastly, in Table 5, the respiration rate errors are reported.…”
Section: Experiments 1-wavelength Selectionmentioning
confidence: 78%
“…As can be observed from performing rPPG using the SPAD camera and the tachogram estimation techniques described in Section 3.3.3, one could retrieve some information on a relatively hard task as remotely estimating the sympathovagal balance. In particular, the best results are achieved at the 550 nm wavelength with a average RMSE of 0.8, which is a state of the art result as reported in [32]. Respiration Rate Lastly, in Table 5, the respiration rate errors are reported.…”
Section: Experiments 1-wavelength Selectionmentioning
confidence: 78%
“…The remote photoplethysmography (rPPG) module 24 is able to analyze heart rate and heart rate variability from videos by the quantifying the amount of light reflected by the face which relates to cardiac cycles and changes in blood volume based on video captured by a camera. 43,65 Gudi et al 66 tested the rPPG system used in the FaceReader TM and found that repetitive facial movements (i.e., in talking conditions) can affect the performance of the system by compromising accurate face modelling and estimations. However, when validated against ECG measurements in video datasets of participants under various conditions (e.g., resting, walking, post-workout), the rPPG system showed promising results.…”
Section: Methodsmentioning
confidence: 99%
“… 43 , 65 Gudi et al. 66 tested the rPPG system used in the FaceReader™ and found that repetitive facial movements (i.e., in talking conditions) can affect the performance of the system by compromising accurate face modelling and estimations. However, when validated against ECG measurements in video datasets of participants under various conditions (e.g., resting, walking, post-workout), the rPPG system showed promising results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations